Reflections Around the Conservation of Sacred Thangkas. Issue 1 (30th October 2013) - Cotte, Sabine
Tibetan thangkas (Buddhist scroll paintings) are created as religious ritual objects. The fact that they are mainly considered as artworks in the Western world impacts on the decisions made for their display and conservation. This article explores the current approach to thangkas in Australian public collections and compares it with the views of contemporary Tibetan Buddhism practitioners. It underlines a few misconceptions at the source of conservation decision-making, and discusses practical outcomes of integrating the sacred dimension into professional practice against the backdrop of conservation's Codes of Ethics. Conserving living religious heritage requires that professional ethical standards are adaptable to the needs of users. Existing frameworks for the conservation of sacred objects of pre-colonised, indigenous cultures provide useful models for the conservation of thangkas. This article argues that engaging with contemporary cultural groups to conserve religious significance is part of the mission of conservators. This is viewed as an expansion of conservation practice into the social realm, in a search for purposeful conservation that establishes the social relevance of our profession.